2011
DOI: 10.1007/s00586-011-1984-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of subaxial cervical foramens: the safety zone for lateral mass screwing

Abstract: AbstractsIntroduction The purpose of this study was to measure the structures of the ventral of lateral masses using cadaver specimens and to quantitatively compare the safety zone for the two major techniques used on each vertebral level from C3 to C6. Methods This study is based on 52 cervical vertebrae of 13 cadavers. The anatomical measurements focused on the anterior surface of the lateral mass. We investigated the safety width, heights, and the height of nerve roots. Results The mean values of the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Morphometric studies using cadavers [11][12][13][14][15] have been reported, which noted the quantitative three-dimensional anatomy of middle cervical regions with measurements of the vertebral bodies, spinal canal, pedicles, lateral masses and transverse foramen. With advances in imaging technology, multiplanar reconstructed CT scans now enable the desired morphology of the cervical spine to be analyzed in three dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric studies using cadavers [11][12][13][14][15] have been reported, which noted the quantitative three-dimensional anatomy of middle cervical regions with measurements of the vertebral bodies, spinal canal, pedicles, lateral masses and transverse foramen. With advances in imaging technology, multiplanar reconstructed CT scans now enable the desired morphology of the cervical spine to be analyzed in three dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…As the placement of such screws may result in VA injury, the location of the VA in the cervical spine must be identified. Although Nishinome et al 3) examined the safety zone for lateral mass screws in 13 cadavers, they did not address the safe distance between the posterior VA surface and the anterior aspect of the lateral mass. Ebraheim et al 2) reported that VA injury can be avoided by screwing perpendicular to the posterior aspect of the lateral mass at C3-C5 and 10° lateral to the sagittal plane at C6 starting at the lateral mass midpoint.…”
Section: Iatrogenic Va Injury During Cervical Spine Surgerymentioning
confidence: 99%
“…Although the risk for VA injury is lower than upon the insertion of pedicle screws, when lateral mass-or transarticular screws are too long or incorrectly directed, the VA may be injured because the vessel is located close to the front of the lateral mass. [1][2][3] Intraoperative lateral Neurologia medico-chirurgica Advance Publication Date: March 5, 2020 perpendicular distance between the posterior VA surface and the posterior line of the vertebral body in 105 patients. We also examined the impact of VA anomalies on the usefulness of the safety line in patients subjected to the insertion of cervical posterior lateral mass-or transarticular screws.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all LSF techniques may result to diverse complications, depending on the surgeon’s optimization of the LSF techniques [ 4 , 5 ]. For the last two decades, many studies have evaluated the advantages of different LSF techniques, based on its complications [ 6 - 8 ]. However, we are unaware of any report that directly compares LSF techniques by analyzing fixation fractures as a severe complication -- which has a relatively low incident rate [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%